2019
DOI: 10.1111/fare.12355
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Activities, Paid Work Interference, and Child Mental Health

Abstract: Objective To examine the association between child mental health and (a) the amount of parent–child interaction and (b) the amount of interference in that interaction due to paid work. Background Although some research findings suggest children do not always benefit from being with their parents full‐time, other studies suggest it is important for children to have their parents' undivided attention. Method Analyses are based on the 2013 New Families in the Netherlands dataset (639 fathers and 849 mothers of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(112 reference statements)
2
3
0
Order By: Relevance
“…These results are consistent with those of Wang and Sheikh-Khalil (2014), who reported that parents' home-based involvement enhances children's mental health. This also confirms the results of Roeters and Van Houdt (2019), who found that fathers' engagement in children's activities promotes children's mental health. Moreover, our results demonstrate that parent-child activities were positively correlated with parents' mental health.…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with those of Wang and Sheikh-Khalil (2014), who reported that parents' home-based involvement enhances children's mental health. This also confirms the results of Roeters and Van Houdt (2019), who found that fathers' engagement in children's activities promotes children's mental health. Moreover, our results demonstrate that parent-child activities were positively correlated with parents' mental health.…”
Section: Discussionsupporting
confidence: 89%
“…This argument is consistent with the notion of work-family goal sequencing, which is necessarily enacted across time (Hirschi et al, 2019), and couples' general need to maintain a feeling of equitable contributions to parenting over time (Radcliffe & Cassell, 2014). Moreover, due to the relatively lax, gendered parenting expectations for fathers compared to mothers (Lam et al, 2012;Roeters & van Houdt, 2019), we posit that fathers will be particularly likely to show day-to-day variation in their parenting behaviour consistent with the notion of compensation.…”
Section: The Spillover From Work Experiences To Parent-adolescent Int...supporting
confidence: 73%
“…Thus, fathers' parenting involvement may be particularly susceptible to both their own work experiences (Almeida et al, 1999; Barnett & Gareis, 2007; Crouter et al, 1999; French et al, 2016) and their partner's inputs to caregiving (Costigan et al, 2003; Vieira et al, 2016). In addition, developmental research suggests that children are more likely to notice changes in fathers' work and parenting behaviour compared to mothers, making fathers' work‐to‐parenting spillover particularly salient and influential (Lam et al, 2012; Roeters & van Houdt, 2019). Furthermore, work–family research suggests that, compared to mothers, fathers may also have difficulty compartmentalizing their work experiences, increasing the likelihood that work spills over to impair their interactions with children (Crouter et al, 1999; Larson & Almeida, 1999; Repetti & Wood, 1997; Shockley et al, 2017).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…, whereas others emphasizing the equal(Hornstra et al, 2022b;Videon, 2005) or higher relevance of biological fathers(Flouri & Buchanan, 2003;Roeters & Van Houdt, 2019). Still, given the strong norms suggesting their particular importance, we argue that biological mothers' involvement has a stronger positive association with child well-being than biological fathers.The strong norms on biological mothers also affect stepparents, particularly stepmothers.…”
mentioning
confidence: 60%